2011
DOI: 10.4236/ajps.2011.21001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomic Study of Some Tribes of Gramineae from Egypt

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…A total of 51 species and 46 genera of grasses were reported from the area. Our findings also agree with that of Perveen and Qaiser 30 , Osman et al, 32 Yen and Yang 20 , who also reported grass species from various parts of the country. As it is clear that no prior work has been done on the grasses in the Charsadda district, hence the current study is a benchmark for future researches.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 93%
“…A total of 51 species and 46 genera of grasses were reported from the area. Our findings also agree with that of Perveen and Qaiser 30 , Osman et al, 32 Yen and Yang 20 , who also reported grass species from various parts of the country. As it is clear that no prior work has been done on the grasses in the Charsadda district, hence the current study is a benchmark for future researches.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 93%
“…Some of the vital taxonomic characters in various taxa of Poaceae are compression-type, hilum position, color and shape of caryopsis [56]. In the present study the caryopsis recorded different shapes ranged from elliptic, oblong, ovate, broad ovate, obovate and rounded which help to distinguish between the studied species, this is in agreement with [36,38]. The color for studied species showed small difference ranging from brown, light brown, to creamy and this partially agree with [35].…”
Section: Discussionsupporting
confidence: 87%
“…Sculpturing of seed plays important role in determining different species [57]. The caryopsis coat pattern sculpturing showed variation ranged from reticulate, rugose, scalariform, striate, reticulate-foveate, reticulate-rugose reticulate-striate, ruminate to striatefavulariate and this is partially agreeing with [38]. Distinct characters at the species level are variations within the anticlinal wall and periclinal wall pattern [58].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…S. suaveolens is an aromatic annual spreading herb from the family Asteraceae with broad sessile leaves covered with glandular hairs (Osman, 2011). The lower stem often trails along the ground and roots at the nodes with thread-like root, flowers are purple, in compound heads ovoid in shape and borne on solitary glandular peduncles with toothed wings (Fayed & Mohamed, 1991).…”
Section: Overview Of S Suaveolens and Its Spatial Distribution In Tan...mentioning
confidence: 99%